Product Purchase Decision Making Process among Urban Married Working Women in Tiruchirappalli District-An Analysis - Sarguna Mary, G. (Indian Journal of Marketing, 2009)
Urban women play a significant role in domestic and socio-economic life of the society. In India, over the years, both female and male roles have been changing. Many women are placing an increasing value on independence and the freedom to do what they want. Being aware of the dual responsibility at home and office, working wives are pressurized for time. As they enjoy economic freedom, it may appear that they make independent decisions. More women are also rejecting traditional roles related to submissiveness and home making. The rise in the importance of Information Technology has given rise to a variety of new professions. They have spawned a taste for a cosmopolitan lifestyle among the emerging middle class. Break-up of joint families, rise in the number of nuclear families and greater urbanization has increased the dependence on household appliances and labour-saving gadgets. In this scenario, women are becoming more visible in the markets and are emerging as the new decision makers at home.